The potential of Kinabalu Hostel as part of core business of Sabah Sport Board / Mohd Hanif Haris - Haris, Mohd Hanif (2011)
The purpose of this study is to investigate the potential of Kinabalu Hostel as part of core business of the Sabah Sport Board. The model was developed on the basis of existing theoretical model focus on marketing and hospitality. The result, factors influencing satisfaction and revisit intentions will act as an input to improve Kinabalu Hostel and Sabah Sports Board performance.